2020
DOI: 10.31083/j.jin.2020.02.32
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin improves memory defects in a mouse model of multiple sclerosis by up-regulating cAMP-response element-binding protein and synapse-associated proteins in the prefrontal cortex

Abstract: Multiple sclerosis is a progressive autoimmune disorder of the myelin sheath and is the most common inflammatory disease of young adults. Up to 65% of multiple sclerosis patients have cognitive impairments such as memory loss and difficulty in understanding and maintaining attention and concentration. Many pharmacological interventions have been used to reverse motor impairments in multiple sclerosis patients; however, none of these drugs improve cognitive function. Melatonin can diffuse through the blood-brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…In a recent work about MS, it was concluded that a combination therapy may be more effective, especially using agents that target neuroinflammation and neurodegeneration, as they may exert synergistic actions, and melatonin is amongst them (Martinez and Peplow, 2020). The effectiveness of melatonin has also been seen to significantly improve memory defects by up-regulating cAMP-response element-binding protein and by increasing the expression of the synapse-associated synaptophysin and postsynaptic density protein 95 genes in the prefrontal cortex (Alghamdi and AboTaleb, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent work about MS, it was concluded that a combination therapy may be more effective, especially using agents that target neuroinflammation and neurodegeneration, as they may exert synergistic actions, and melatonin is amongst them (Martinez and Peplow, 2020). The effectiveness of melatonin has also been seen to significantly improve memory defects by up-regulating cAMP-response element-binding protein and by increasing the expression of the synapse-associated synaptophysin and postsynaptic density protein 95 genes in the prefrontal cortex (Alghamdi and AboTaleb, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we thus used the highest prophylactic dose of MLT (80 mg/kg), which does not produce any signs of toxicity in mice. 14 , 18 , 66 This high dose of MLT is found to be a potent antioxidant and anti-inflammatory which improved memory outcomes and locomotor activity in multiple sclerosis animal model. 14 , 18 Moreover, this high dose of MLT altered the T effector/regulatory balance which therefore protect against experimental autoimmune encephalomyelitis animal model.…”
Section: Discussionmentioning
confidence: 96%
“…We used the highest prophylactic dose of MLT (80 mg/kg), which does not produce any signs of toxicity in mice. 14 , 18 , 47 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin (MLT) is a neurohormone secreted from the pineal gland and extra-pineal sources that exhibits a wide variety of regulatory functions ( Alghamdi, 2018 ). One previous study reported that MLT enhanced memory by upregulating synapse-associated synaptophysin and postsynaptic density protein 95 genes in the prefrontal cortex ( Alghamdi and AboTaleb, 2020 ). Other studies found that MLT can improve memory impairment though brain-derived neurotrophic factor/cAMP-response element binding protein expression in AD mice ( Labban et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%